Pengaruh Profitabilitas dan GCG terhadap Nilai Perusahaan Indeks LQ45 di BEI Tahun 2018-2022 - Dara Aprilly, Rosa Virginia; Sadikin, Dikdik Saleh (Jurnal Keuangan dan Perbankan, 2024)
This study aims to determine and analyze the influence of Profitability and Good Corporate Governance (GCG) on company value in LQ45 Index companies listed on the BEI for the period 2018 to 2022. The sample in this study used a purposive sampling method, with the number of samples in this study being namely 24 companies listed on the Indonesian Stock Exchange (BEI). The dependent variable used is Firm Value (PBV), then the independent variables are Profitability (ROA) and Good Corporate Governance (GCG) which is proxied by Managerial Ownership, Institutional Ownership and Independent Board of Commissioners. The research results show that Profitability (ROA) and Institutional Ownership have a significant positive effect, while Managerial Ownership and the Independent Board of Commissioners do not have a significant effect on Firm Value.